Age-Related Effects of Physical Performance on Technical and Tactical Outcomes in Youth Soccer - Patrik Hegedüs; Dániel Csala; János Tóth; János Tóth (Sports, 2025)
This study explores how age influences the relationship between physical performance (PP) and technical–tactical parameters (TPs) in youth soccer, analyzing 80 matches across four age groups: U15, U17, U19, and NB1 (adults). Team-level data were examined to assess how maturation affects the integration of physical and technical demands. Physical metrics included total distance (TD) and total high-intensity distance (THID), while TP metrics involved actions such as pressing, tackling, and ball possession. Pearson’s correlations and general linear models (GLMs) were used to identify associations between PP and TPs across age categories. The results showed age-related trends in performance integration. U19 and NB1 players demonstrated moderate-to-strong correlations between PP and TP variables, with TD and THID positively associated with pressing and tackling, indicating increasing synergy with age. U17 players showed emerging integration, while U15 players exhibited no significant correlations, suggesting developmental variability. Limitations include reliance on team-level correlational data and the absence of individual physiological or cognitive assessments. These findings suggest that training approaches should be tailored to players’ developmental stages, with increasing emphasis on combining physical conditioning and tactical understanding as players mature.